O uso de jogos educacionais para a aprendizagem de programação no ensino fundamental - Widthauper, Meikon Rodrigo (2020)
Each individual is not endowed with the same set of skills, consequently, not everyone learns the same way, according to Gardner's theory of multiple intelligences (1985). Therefore, it is up to the educator to discover alternatives that help in this process. This article proposes the use of educational games to assist in teaching programming in the computer classes of the initial series. Bringing an alternative that helps and facilitates the life of the educator, through a platform called the Hour of the Code that has several games with playful and current themes that catch the children's attention, aiming to carry out a feasibility study of the introduction of programming languages, in elementary school, through workshops, so that students can already get used to small codes, using block language, to make the content more attractive and easy to understand. Seeking to disseminate the importance of codes for the future of students and to make them more prepared for the job market.